The Influence of Soft Skills, Adversity Quotient, and Self Efficacy on Work Readiness in Students of The 2020 Class of Management Study Program, Universitas Muhammadiyah Malang - Ambarwati Setyoningrum; Rizki Febriani; Ratya Shafiraa; Nur Yudiono (Universitas muhammadiyah malang, 2024)
The purpose of this study was to determine the effect of soft skills, adversity quotient and self-efficacy of students on work readiness. The study population was Management Study Program students, University of Muhammadiyah Malang, Class of 2020. Sampling using the Slovin formula method with basic random sides resulted in 86 responses. Multiple linear regression analysis was carried out using SPSS 26 in this method. The findings of this study indicate that although adversity quotient has a positive and insignificant effect on work readiness—that is, it does not affect students' readiness to enter the workforce—skills have a large positive effect on work readiness. Work readiness increases significantly through self-efficacy. In management study program students, University of Muhammadiyah Malang, Class of 2020, self-efficacy has a stronger influence on work readiness.